Social Evaluation of Accused and Victims of Assault and Battery - Büken, Bora; Günay, Yasemin; Birincioğlu, İsmail; Katkıcı, Ufuk (The Bulletin of Legal Medicine, 1997)
In this study demographic findings obtained from a survey among 306 victims of assault and battery who were referred in the Department of the Council of Forensic Medicine in the municipality of Sivas between June 15 and December 15, 1995, are presented. Comparing the age distribution of both the victims and accused, the two groups were most frequently represented in the 3 rd decade. Males accounted for 81.3 % of the victims and 89.1 % of the accused. Educational level was primary school and below in 47.4 % of the victims and 51.9 % of the accused, respectively. 34.6 % of the victims and 27.9 % of the accused were unemployed or housewifes. In 46.7 % there was infliction of blunt trauma without using an instrument, while the ratio was 30.7 % in cases which an instrument was used for trauma infliction. The assault took place in 48.3 % of the cases in common places and in 31.4 % in domestic locations. In 59.4 % of the cases more than two persons participated in the assault; and victim and accused did not know each other in 30.0 % of the cases, whereas in 21.3 % the assault took place among relatives and in 6.7 % between married couples. The most frequent motive was found to be financial problems and insult.Key words: Assault and battery, victim, accused, demographic findings.
Keywords: assault and battery; victim; accused; demographic findings